The link between intrauterine adhesions and impaired reproductive performance: a systematic review of the literature - Angelo B. Hooker; Robert A. de Leeuw; Mark Hans Emanuel; Velja Mijatovic; Hans A. M. Brolmann; Judith A.F. Huirne (figshare, 2022)
Abstract Background Intrauterine adhesions (IUAs) are one of the main reproductive system diseases in women worldwide. Fusion between the injured opposing walls leads to partial-to-complete obliteration of the cavity and/or cervical canal. The main clinical manifestations in case of IUAs are menstrual disturbances, cyclic pain and reproductive disorders. The reproductive outcomes of women with IUAs remain limited and inefficient compared to women without IUAs, even after adhesiolysis. An exact understanding of the underlying mechanisms and processes to explain the compromised reproductive performance and outcomes in case of IUAs are lacking. Methods A systematic literature review of MEDLINE-PubMed (1966 to January 2022) and EMBASE (1974 to January 2022) was performed following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies were included if they reported underlying causes, related mechanisms and processes to explain the association between IUAs and impaired reproductive performance, pregnancy and obstetric complications. Results After an extensive review of the literature, 58 articles were identified reporting underlying mechanisms to explain the association between IUAs and impaired fertility. Intrauterine scarring influences the process of fertilization, reproductive performance and ultimately reproductive outcome. IUAs can disturb the cervico-utero-tubal sperm transport and result in an avascular and unresponsive endometrium with decreased receptivity and thickness. Abnormal decidualization and abnormal trophoblastic infiltration leads to placental attachment disorders. Moreover, the risk for premature delivery, intrauterine fetal growth restriction and fetal anomalies is increased in case of IUAs. Conclusion The impact of IUAs on reproductive performance, even after adhesiolysis, is becoming more apparent. The postulated mechanisms to explain the association are related to sperm transport, embryo implantation and placentation. Prevention, by preserving the basal layer of the endometrium is essential. Effective and evidence-based strategies for the prevention of endometrial injury and formation of IUAs, are urgently needed.
Keywords: Medicine; Cell Biology; Genetics; Physiology; Sociology; Cancer